IDH1: Linking Metabolism and Epigenetics - Raineri, Silvia; Mellor, Jane (Frontiers in Genetics, 2018)
Mutations in genes encoding enzymes of the Tricarboxylic Acid Cycle often contribute to cancer development and progression by disrupting cell metabolism and altering the epigenetic landscape. This is exemplified by the isoforms of Isocitrate Dehydrogenase (IDH1/2), which metabolize Isocitrate to α-Ketoglutarate (α-KG). Gain of function mutations in IDH1 or IDH2 result in reduced levels of α-Ketoglutarate as a result of increased formation of D-2-Hydroxyglutarate (2-HG). α-KG is an essential co-factor for certain histone and DNA demethylases, while 2-HG is a competitive inhibitor. These IDH1/2 mutations are thought to result in hypermethylated histones and DNA which in turn alters gene expression and drives cancer progression. While this model seems to be generally accepted in the field, the exact molecular mechanisms still remain elusive. How much of this model has been rigorously demonstrated and what is just being assumed? Are the effects genome-wide or focused on specific loci? This Perspective aims at elucidating the key questions that remain to be addressed, the experimental techniques that could be used to gain further insight into the molecular mechanisms involved and the additional consequences of these mutations beyond DNA and protein methylation.